2020
DOI: 10.1111/ter.12450
|View full text |Cite
|
Sign up to set email alerts
|

Three‐dimensional vorticity and time‐constrained evolution of the Main Central Thrust zone, Garhwal Himalaya (NW India)

Abstract: Vorticity estimates based on porphyroclasts analysis are limited by the extrapolation to three dimensions of two‐dimensional data. We describe a 3D approach based on the use of X‐ray micro‐computed tomography that better reflects the real 3D geometry of the porphyroclasts population. This new approach for kinematic vorticity analysis in the Munsiari Thrust mylonites, the lower boundary of the Main Central Thrust zone (MCTz) in Indian Himalaya, indicates a large pure shear component during non‐coaxial shearing.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 52 publications
5
21
0
Order By: Relevance
“…The Himalayas has been the focus of a large number of geodynamic models that make predictions regarding the paths that rocks follow during collision (Beaumont et al., 2001; Burg & Podladchikov, 2000; Carosi et al., 2018; Guillot & Allemand, 2002; Imayama et al., 2010; Larson et al., 2013; Li, 2014; Montemagni et al., 2020; Rolfo et al., 2014; Searle et al., 2017; Waters, 2019; Yin, 2006). However, the primary focus of many models of Himalayan development has been the GHC, and the majority of the P‐T paths we obtained are from the MCT footwall.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The Himalayas has been the focus of a large number of geodynamic models that make predictions regarding the paths that rocks follow during collision (Beaumont et al., 2001; Burg & Podladchikov, 2000; Carosi et al., 2018; Guillot & Allemand, 2002; Imayama et al., 2010; Larson et al., 2013; Li, 2014; Montemagni et al., 2020; Rolfo et al., 2014; Searle et al., 2017; Waters, 2019; Yin, 2006). However, the primary focus of many models of Himalayan development has been the GHC, and the majority of the P‐T paths we obtained are from the MCT footwall.…”
Section: Discussionmentioning
confidence: 99%
“…The P-T paths themselves require footwall imbrication, and the model suggests the outlined parameters are appropriate for rocks from both the Marsyangdi and Bhagirathi river transects. Other models anticipate similar behavior in the MCT shear zone (e.g., Braden et al, 2018;Caddick et al, 2007;Groppo et al, 2009;Herman et al, 2010;Imayama et al, 2020;Larson et al, 2015;Montemagni et al, 2020;Mosca et al, 2012;Mottram et al, 2014). The Theriak-Domino P-T paths from both the Bhagirathi and Marsyangdi regions cannot develop if only a single phase of Miocene MCT motion is imposed.…”
Section: Modeling Lhf P-t Paths and Monazite Agesmentioning
confidence: 94%
See 1 more Smart Citation
“…But, many recent studies seriously questioned their contemporaneous relation (Kohn, 2008;Carosi et al, 2013;Finch et al. 2014;Weinberg, 2016;Iaccarino et al, 2017Montemagni et al, 2019;Montemagni et al, 2020). It has been shown that the STDS initiated before 24-25 Ma (Figure 8A), as reported from western FIGURE 8 | (A) Graphical plots of the geological ages of GHS exhumation and associated crustal scale shear zones (STDS, HHD, and MCT) in the Himalaya, compiled from available recent literature (I17: Iaccarino et al, 2017;Slr18: Soucy La Roche et al, 2018;L15: Leloup et al, 2015;M13: Montomoli et al, 2013;Z15: Zeiger et al, 2015;A16: Agustsson et al 2016;S17: Shrestha et al, 2017;K10: Kellet et al, 2010;F14: Finch et al 2014;Ca13: Carosi et al 2013;W16: Wang et al, 2016;K19: Kellett et al, 2019;Mg18: Montemagni et al, 2018;Ca18: Carosi et al 2018).…”
Section: Initiation Time Of the Wedge Extrusionmentioning
confidence: 99%
“…Several studies demonstrated that extension along the STDS and thrusting along the MCT initiated synchronously during Early Miocene at~23 Ma (e.g., Dèzes et al, 1999;Godin et al, 2006;Hodges et al, 1992Hodges et al, , 1996. This common view is however challenged by structural and geochronological data revealing that, in central Nepal, the onset of the exhumation of the HHC took place before (middle-late Eocene) the period of MCT and STDS activity (Carosi et al, 2013(Carosi et al, , 2016Iaccarino et al, 2017;Montemagni et al, 2020). Movements along both the MCT and the STDS nevertheless suggest a southward tectonically controlled extrusion of the high-grade paragneiss of the HHC (Hodges et al, 1992;Vannay et al, 2004;Vannay & Grasemann, 2001).…”
Section: Geological Settingmentioning
confidence: 99%